PENGARUH LAPORAN KEUANGAN TERHADAP PENGAMBILAN KEPUTUSAN BERINVESTASI DI GALERI INVESTASI SYARIAH FEBI IAIN PALANGKA RAYA - M. Ihsan Nur Rasid; Muhammad Riza Hafizi (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2022)
Financial statements are one of the indicators that can provide an overview of the circumstances or conditions of an issuer through financial ratios, namely profitability, solvency, and value to investors in making an investment decision. In addition, financial knowledge is also one of the indicators that can influence investors in making investment decisions. The purpose of the study was to find out how much influence the issuer's financial statements have on investment decision making in the Sharia Investment Gallery FEBI IAIN Palangka Raya. The study uses a quantitative approach with expost facto types of research. The method of data collection in this study uses questionnaires and documentation. The sample in this study amounted to 83 people who were registered as customers at the Sharia Investment Gallery FEBI IAIN Palangka Raya from 2018-2020. Sampling in this study used proportional claster random sampling with solvin formula and a tolerance value of 10%. The data analysis technique used is regression analysis with the help of SPSS Statistics 26. Regression analysis results showed that the significance value of 0.000 < 0.05 and the known t value of This numera 5.103 > 1,990. Overall it can be concluded that Ho was rejected and Ha was accepted, namely ada significant influence between the issuer's financial statements on investment decision making in the Sharia Investment Gallery FEBI IAIN Palangka Raya. Based on the value of the coefficient of determination (R Square) obtained by 0.243 which contains the understanding of the effect of free variables (independent/financial statements) on bound variables (dependents/investing decision making) is 24.3%, and the remaining 75.7% is influenced by other factors that are not contained in the researcher's research.